Changes in Spatial Planning and the Destruction of City Identity: Lasem Case during 1970-1991 - Retna Dyah Radityawati; Singgih Tri Sulistiyono; Endang Susilowati (IHiS (Indonesian Historical Studies), 2020)
This article aims to examine the factors and driving forces for Lasem City's spatial changes during 1970-1991. The changes were attributed to the New Order Government's policy regarding road infrastructure development to support the economy. In addition, there were policies during the New Order era which tended to discriminate against ethnic Chinese. These policies were carried out under the pretext of affiliation with communism among members of the Chinese community. This caused some Lasem residents to choose to abandon their Chinese identity. Data collection for this study employed the historical method consisting of four stages: heuristics, source criticism, interpretation, and historiography. Based on research, the development agenda of the New Order era that failed to take into account the aspect of sustainability eroded the identity of the City of Lasem as a place teeming with cultural life.